Think yourself rich use the power of your subconscious mind to find true wealth - Murphy, Joseph 1898-1981 (Prentice Hall, 2001)
Dr. Joseph Murphy, one of the world's best-known authorities on the power of the subconscious mind, shows readers not only how to unleash this power, but how to harness it and effectively use it to change their lives. Fully updated to reflect the sensibilities of the 21st century, this revised edition of a self-help classic is the key to overcoming the psychological barriers that stand in the way of greater material, spiritual, and emotional wealth.